Fosfomycin: An old antibiotic and new perspectives. A review - Marina V. Leonova (ZAO "Consilium Medicum", 2023)
Urinary tract infection (UTI) is one of the most common urological diseases and presents a problem for rational antibiotic therapy due to the growing antibiotic resistance. Fosfomycin is one of the older low molecular weight, broad-spectrum bactericidal antibiotics with activity against uropathogens, particularly Escherichia coli and others. Fosfomycin is administered as a single dose that achieves very high concentrations of the antibiotic in the urine and bladder, sufficient to eliminate most common uropathogens, including those with multidrug resistance (MDR). Many factors have contributed to the persistence of fosfomycin's antibacterial activity, including the use of a single dose, limited use for UTIs only, and very high and persistent urinary concentrations that rapidly kill bacteria, reducing the possibility of mutant selection. In addition to its antimicrobial properties, fosfomycin has an immunomodulatory effect by altering the function of lymphocytes, monocytes, and neutrophils. It affects the acute inflammatory cytokine response. New data have been obtained on the activity of fosfomycin against biofilms formed by uropathogens and against biofilm-associated bacterial strains with MDR. A new 2020 meta-analysis compared the efficacy of fosfomycin with equivalent antibiotics (β-lactams/cephalosporins, quinolones, sulfonamides, nitrofurantoin) in women in the broad categories of uncomplicated UTI or asymptomatic bacteriuria and found no difference in clinical and microbiological cure rates with comparison groups. A number of other studies in patients with UTIs with MDR or complicated course also showed a high sensitivity of uropathogens to fosfomycin and the effectiveness of treatment with multiple doses (2-3 doses with an interval of 48-72 hrs). Fosfomycin is being considered as a potentially useful antibiotic for the treatment of prostatitis. Current data indicate that sufficient concentrations in prostate tissue are achieved after a single dose of fosfomycin. Recent reviews in 2019 and 2022 present results of studies of fosfomycin for the prevention of infectious complications after transurethral prostate biopsy and in patients with chronic bacterial prostatitis whose pathogens are resistant to other antibiotics. Thus, the accumulation of new scientific data on the mechanisms of action and resistance of fosfomycin reveals more potential advantages of its practical application.